Speech and language intervention in bilinguals - Ramos, Eliane; Ardila, Alfredo (Revista de Investigación en Logopedia, 2011)
Increasingly, speech and language pathologists (SLPs) around the world are faced with the unique set of issues presented by their bilingual clients. Some professional associations in different countries have presented recommendations when assessing and treating bilingual populations. In children, most of the studies have focused on intervention for language and phonology/ articulation impairments and very few focus on stuttering. In general, studies of language intervention tend to agree that intervention in the first language (L1) either increase performance on L2 or does not hinder it. In bilingual adults, monolingual versus bilingual intervention is especially relevant in cases of aphasia; dysarthria in bilinguals has been barely approached. Most studies of cross-linguistic effects in bilingual aphasics have focused on lexical retrieval training. It has been noted that even though a majority of studies have disclosed a cross-linguistic generalization from one language to the other, some methodological weaknesses are evident. It is concluded that even though speech and language intervention in bilinguals represents a most important clinical area in speech language pathology, much more research using larger samples and controlling for potentially confounding variables is evidently required.
Keywords: Aphasia; Bilingualism; Phonological disorders; Speech impairments; Stuttering; Therapy.